2018
DOI: 10.1111/ejn.13962
|View full text |Cite
|
Sign up to set email alerts
|

Neuroplasticity in cholinergic neurons of the laterodorsal tegmental nucleus contributes to the development of cocaine addiction

Abstract: The laterodorsal tegmental nucleus (LDT) is a brainstem nucleus that sends cholinergic, glutamatergic, and gamma-aminobutyric acid (GABA)-ergic projections to the ventral tegmental area (VTA), a key brain region associated with reward information processing and reinforcement learning, and thus, with addiction induced by drugs of abuse, including cocaine. Recent studies have revealed that the LDT, in addition to the VTA, plays important roles in the development and expression of cocaine-induced addiction and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 138 publications
(205 reference statements)
0
9
0
Order By: Relevance
“…Even so, there is electrophysiological evidence that nicotine enhances the excitability of cholinergic and noncholinergic LDTg neurons (Ishibashi, Leonard, & Kohlmeier, ; Polli & Kohlmeier, ). Thus, it is well conceivable that neuroplasticity in cholinergic IP‐projecting LDTg neurons is involved in the regulation of reward circuitry, as it has been shown by optogenetic approaches for cholinergic and glutamatergic LDTg projections targeting the VTA (Dautan et al, ; Kaneda, ; Lammel et al, ; Steidl, Wang, Ordonez, Zhang, & Morales, ).…”
Section: Discussionmentioning
confidence: 99%
“…Even so, there is electrophysiological evidence that nicotine enhances the excitability of cholinergic and noncholinergic LDTg neurons (Ishibashi, Leonard, & Kohlmeier, ; Polli & Kohlmeier, ). Thus, it is well conceivable that neuroplasticity in cholinergic IP‐projecting LDTg neurons is involved in the regulation of reward circuitry, as it has been shown by optogenetic approaches for cholinergic and glutamatergic LDTg projections targeting the VTA (Dautan et al, ; Kaneda, ; Lammel et al, ; Steidl, Wang, Ordonez, Zhang, & Morales, ).…”
Section: Discussionmentioning
confidence: 99%
“…Blockade of glutamatergic AMPA receptors in a region of the brainstem encompassing the LDT, which should inhibit LDT excitability, was shown in vivo to attenuate reinstatement of drug seeking induced by cocaine injection, an effect also observed after intra-VTA blockage of AMPA, nAChR, and mAChR receptors, suggesting that ACh output from the LDT was involved, with perhaps a contribution from glutamatergic LDT output, and further, that excitatory glutamatergic activity within the LDT was important for drug induced behaviors (Schmidt et al, 2009). A role for glutamatergic activity in the LDT in drug-addiction-associated behaviors was also indicated by intra-LDT pharmacologic blockade of AMPA and NMDA receptors in vivo which attenuated cocaine CPP (Shinohara et al, 2014;Kaneda, 2019). This attenuation reached its maximum effect following intra-LDT application of carbachol, which hyperpolarizes LDT neurons when acting at mAChRs, leading to a profound inhibition (Shinohara et al, 2014;Kaneda, 2019).…”
Section: Ldt-vta Inputsmentioning
confidence: 94%
“…A role for glutamatergic activity in the LDT in drug-addiction-associated behaviors was also indicated by intra-LDT pharmacologic blockade of AMPA and NMDA receptors in vivo which attenuated cocaine CPP (Shinohara et al, 2014;Kaneda, 2019). This attenuation reached its maximum effect following intra-LDT application of carbachol, which hyperpolarizes LDT neurons when acting at mAChRs, leading to a profound inhibition (Shinohara et al, 2014;Kaneda, 2019). Finally, a study of the role of the functional significance of the LDT-VTA pathway in addiction-related behaviors and signaling provided probably the first indication that drugrelated plasticity can occur in the LDT, albeit this was not the focus of the study.…”
Section: Ldt-vta Inputsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, evidence linking the nucleus accumbens shell to extinction and reinstatement of drug seeking sheds light on known heterogeneities in nucleus accumbens shell cell types, and their major afferents and efferents, suggesting that the functional specialization of the nucleus accumbens shell should be viewed in terms of the segregation and compartmentalization of its channels (Gibson et al ., ). Summarizing recent progress, it is suggested that cocaine‐induced neuroplasticity in the laterodorsal tegmental nucleus (a brainstem nucleus that sends cholinergic, glutamatergic and GABAergic projections to the VTA) cholinergic neurons contributes to the development and modulation of cocaine‐related addictive behaviours (Kaneda, ). In the contribution from di Volo and colleagues, an interesting computational approach is taken to delineate potential circuit‐level mechanisms responsible for alcohol‐dependent dysregulation of DA release from the VTA into its projection areas (di Volo et al ., ).…”
Section: Reviewsmentioning
confidence: 99%